PENGARUH BLOG EDUKATIF TENTANG DIABETES MELITUS (DM) TERHADAP INDEKS MASSA TUBUH (IMT) PENDERITA DIABETES MELITUS DI PUSKESMAS WIROBRAJAN YOGYAKARTA - Isra Nur Utari Syachnara Potabuga; Erfin Firmawati (Journal of Advanced Nursing and Health Sciences, 2021)
Diabetes Mellitus (DM) was often known as "The great imitator" because the diseasecan affect and attack all organs and cause a variety of complaints with signs and symptoms variety greatly. Diabetes Mellitus Sufferer in Indonesia is predicted to increase the amount of 8,4 million in 2000 to around 21,3 million in 2030. The Educative blog about DM is an innovation to provide health information and education program that benefit for DM sufferer. The purpose of this study was to know the effect of educative blog about DM toward Body Mass Index (BMI) on DM sufferer in Wirobrajan Public Helath Center. Kind of this research is Quasy Experiment with design two group pre-post test with control group. The sampling technique on this research with Purposive Sampling and obtained 40 respondents. Twenty respondents on the experimental group and 20 respondents on control group. Data analysis used the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The result of Wilcoxon Signed Rank Test showed a significant difference after being given educative blog intervention on the experimental group blog with p = 0,00. For the Mann-Whitney U test found in the IMT pre-test p = 0.13 and post-test p = 0.00.The conclusion of this research is that there is effect educative blog about DM toward IMT with a significance value of the Mann-Whitney U test, namely p = 0,00 or < 0.05.